If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + 2(1 + -7b) = -86 3b + (1 * 2 + -7b * 2) = -86 3b + (2 + -14b) = -86 Reorder the terms: 2 + 3b + -14b = -86 Combine like terms: 3b + -14b = -11b 2 + -11b = -86 Solving 2 + -11b = -86 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -11b = -86 + -2 Combine like terms: 2 + -2 = 0 0 + -11b = -86 + -2 -11b = -86 + -2 Combine like terms: -86 + -2 = -88 -11b = -88 Divide each side by '-11'. b = 8 Simplifying b = 8
| 10y+15x= | | 2-55+(65+85)=5 | | 3x^2-23xy+40xy^2=0 | | 3x^2-20xy+40xy^2=0 | | (12(-0.5)+3)= | | 7z+3=38 | | 3(q-5)=2(q-15) | | (11(-0.5)+9)= | | 21x-x= | | (11x+9)+(12x+3)=0 | | 1000=30x | | 36x-10(x+2)=13-7x | | (11x+9)+(12x+3)=o | | 24-3u=2u | | 4(-2)+3y=12 | | f(x)=8x^3-12x^2-36x | | 2x+1y=3.55 | | (x+8)(8-x)= | | 2x+1b=3.55 | | 4c+3(5)=12 | | 14d-8=6d | | 7h-8=41 | | 1650h-25=1325 | | 2x-3(x+4)=-16 | | 16+8v=54 | | 2x-7(8)=x+10(4) | | 11k^2-14k-16=0 | | 11k^2-14-16=0 | | 172.8n=(n-2)*180 | | 3y+10=-14 | | 11k^2-14k+16=0 | | 162n=(n-2)*180 |